Antioxidant effect of Abelmoschus Esculentus against acetaminophen-induced nephrotoxicity: an experimental study - Mervan Bekdas; Arzu Meyri Yoldas; Aysegul Danıs; Selma Erdogan Duzcu; Murat Alisik; Ayhan Cetinkaya; Huseyin Kocabey; Idris Turel; Mustafa Dilek; Gokce Kaya Dincel (Universitas Muhammadiyah Yogyakarta, 2022)
Acetaminophen(APAP) intoxication is an important cause of nephrotoxicity and hepatotoxicity. N-acetylcysteine(NAC) is used in the treatment, but it has some serious side effects. Abelmoschus esculentus(AE) has various benefits as well as antioxidant effects. This study aims to investigate the effect of AE in APAP-induced acute nephrotoxicity. Forty male Wistar rats were divided into five equal groups: Control, AE, APAP, APAP+AE, and APAP+AE+NAC. Significant changes were observed in serum levels of malondialdehyde (MDA), superoxide dismutase (SOD), Neutrophil Gelatinase-Associated Lipocalin(NGAL) and Kidney Injury Molecule-1(KIM-1) after induction with APAP. NGAL and KIM-1 in the AE group remained low compared to those receiving APAP (p=0.022 and p0.001, respectively). When the APAP group was compared with the AE and AE+NAC groups, it was found that even the administration of AE alone significantly decreased NGAL and KIM-1(p=0.036 vs.p=0.029 and p0.001 vs. p0.001, respectively), these results were attributed to the effects of AE on reducing MDA and increasing SOD. Histopathological studies also confirmed these results. These results demonstrated that AE had protective and therapeutic effects on APAP-induced nephrotoxicity. This benefit of AE is due to its antioxidant effect. In addition, AE may also increase the regenerative capacity of the kidney, which APAP reduces.